Experiences of Indian Immigrant Teachers in New Zealand Early Childhood Centres - Kaur, Amrit (Auckland University of Technology, 2018)
Teachers have migrated from one country to another for many years, in many cases to very different cultural environments, and consequently, they often face major challenges in cultural adaptation. Such adaptation may be necessary if they are to perform their jobs appropriately, as cultural competence is necessary for teachers to deliver quality and effective education to their students in the country of migration. The adaptation process is more difficult when the teachers move from their own culture and environment to one that is vastly different. This qualitative narrative study examined the lived experiences of teachers who have emigrated from India to New Zealand and are working in early childhood centres. The participants were qualified early childhood education (ECE) teachers in ECE centres in Auckland, New Zealand. The teachers were invited to join this study via professional and personal contacts. Semi-structured interviews with open-ended questions were conducted with 15 Indian early childhood education teachers, to determine the challenges, obstacles and benefits in the process of cultural adaptation. The chosen narrative, qualitative study approach, was deemed most appropriate for this study because its goal is to examine a phenomenon using the lived experiences shared by the immigrant teachers. The data gathered from the interviews was coded and classified with emergent, recurrent, and dominant themes identified. The main finding from this study showed that participants have unique characteristics in that in most cases, the language barrier to assimilation was small or non-existent, while other cultural differences such as beliefs, values, lifestyle, customs and traditions were significant. It is anticipated that the findings of this study could serve as a suggestion to make the cultural transition process easier for these teachers, as well as the ones who come after them on the same path.
Keywords: Indian immigrant; Strategies; Approaches; Early childhood teachers; Culture sensitivity